2005
DOI: 10.1061/(asce)0733-9445(2005)131:11(1665)
|View full text |Cite
|
Sign up to set email alerts
|

Dry Joint Stone Masonry Walls Subjected to In-Plane Combined Loading

Abstract: The paper presents the results of experimental research on the structural behavior of dry joint masonry. The most relevant experimental results concern the strength response of stone dry joint masonry walls subjected to in-plane combined compressive and shear loading. Significant features of the structural behavior shown by the walls are discussed and conclusions on their ultimate capacity and observed failure mechanisms are addressed. Complementarily, the application of an existing numerical model, stemming f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
88
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(98 citation statements)
references
References 10 publications
9
88
0
1
Order By: Relevance
“…The failure envelope used in this study was the Mohr-Coulomb criterion with a tension cut-off. This model existed in the discrete element code; its relevance was checked in the case of masonry walls [20]. The Mohr-Coulomb criterion is expressed in terms of the principal stresses σ 1 , σ 2 , and σ 3 , which constitute the three components of the generalized stress vector for this model (n = 3), whereby the three principal stresses are: σ 1 ≤ σ 2 ≤ σ 3 .…”
Section: Constitutive Behavior Of Earthen Layers (Blocks)mentioning
confidence: 99%
“…The failure envelope used in this study was the Mohr-Coulomb criterion with a tension cut-off. This model existed in the discrete element code; its relevance was checked in the case of masonry walls [20]. The Mohr-Coulomb criterion is expressed in terms of the principal stresses σ 1 , σ 2 , and σ 3 , which constitute the three components of the generalized stress vector for this model (n = 3), whereby the three principal stresses are: σ 1 ≤ σ 2 ≤ σ 3 .…”
Section: Constitutive Behavior Of Earthen Layers (Blocks)mentioning
confidence: 99%
“…On the other hand, experimental studies are usually rare because difficult to undertake : in the literature can be found laboratory tests on periodic masonry [9] as well as recent on-site experiments on dry-stone retaining walls [10,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…A brick masonry wall was analyzed in static and dynamic loadings and found capable to predict appropriate response. Using similar approaches, Lourenco et al [7] and Senthivel et al [8] investigated on dry joint cut sawn stone masonry walls to verify the experimental investigations. This concept has also been applied to investigate the effectiveness of wooden bond beams in dry stone masonry houses [9].…”
Section: Description Of Numerical Methodologymentioning
confidence: 99%
“…2), and corresponding stiffness matrix for zero thickness joint elements is given in Eqs. (2) and (3) as formulated by Tzamtzis and Nath [4][5][6][7]: [7] which leads the Eqs. (4) and (5):…”
Section:  mentioning
confidence: 99%